PENGARUH KOMUNIKASI ORANGTUA DENGAN GURU TERHADAP PROSES PENINGKATAN KUALITAS BELAJAR PADA SISWA KELAS V SEMESTER GENAP SD NEGERI 1 BERINGIN RAYA - Tanod, Mareyke Jessy; Diswantika, Noviana (LPPM STKIP PGRI Bandar Lampung, 2020)
This study aims to determine: 1. Communication between teachers and parents at SD Negeri 1 Beringin Raya, 2. A description of the quality of learning at SD Negeri 1 Beringin Raya. The study was conducted with a qualitative method approach. The research variables consisted of parent and teacher homeroom teacher communication and learning quality. The sample of this research is the fifth-grade students of SD Negeri 1 Beringin Raya, the subject of this study is the homeroom teacher and the principal The data collection methods in this study were interviews and observations. Based on the results of the study it can be seen that there is a lack of communication between teachers and guardians of students at SD Negeri 1 Beingin Raya. This shows that the influence of communication between parents and teachers is not good, because they do not have openness, empathy, support, positive feelings, parents give full responsibility to teachers at school. The effect of communication between people and teachers on improving the quality of learning that is of poor quality, Quality of learning media, and Learning Systems in schools. The description of the influence of parent and teacher communication on improving the quality of learning in class V in SD Negeri 1 Beringin Raya is in the less strong category, it shows that when the communication between parents and teacher is not good. The quality of learning in class V is good but if the parents' communication with the teacher does not go well then the effect is not good on the quality of learning for students.